Ответы и объяснения

Лучший Ответ!
2012-07-05T13:21:57+04:00

\\(x-3)^{10}(x-1)^{9}x^{4}(x+2)\leq0

Решим неравенство методом интервалов 

Найдем точки, при которых выражение   \\(x-3)^{10}(x-1)^{9}x^{4}(x+2)  превращается в нуль.

\\(x-3)^{10}(x-1)^{9}x^{4}(x+2)=0 \\x_{1}=3, x_{2}=1, x_{3}=0, x_{4}=-2 

 

     +       -         -        +              + 

 ------ -2 -------0--------1----------3------------>x 

 

Ответ: x\in[-2;1]

 

2012-07-05T18:00:27+04:00

(х-3)¹⁰(х-1)⁹х⁴(х+2)≤0

х₁=3;х₂=1;х₃=0;х₄-2

  +      -              -           +                 +     
   -2          0             1              3               х

 Ответ:х€[-2;1].